Post-Operative Outcome of Open Cholecystectomy in Patients Receiving Spinal Versus General Anesthesia - Imran Hafeez, Maqsood Ahmed Siddiqui, Imran Ali, Kelash Kumar, Ahmed Uddin Soomro, Aqil Qayoom (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The purpose of this study was to analyze the postoperative outcome of open cholecystectomy in patients receiving spinal versus general anesthesia. Study design: Analytical cross-sectional study Place and Duration: this studay was conducted in King Abdullah Medical City Makkah Kingdom of Saudi Arabia from January 2020 to January 2021. Methodology: A total of 180 patients that had the surgery of open cholecystectomy under spinal as well as general anesthesia were included in this research. All patients who had pancreatitis, contraindication to spinal anesthesia or general anesthesia, or severe cardiopulmonary diseases were excluded from the study. Patients were randomly distributed into two groups which are SA and GA groups, with each group having 90 patients. The sample size was determined via open epi. After the surgical procedure, patients were followed and analyzed for postoperative outcomes. Results: A total of 140 patients were female while 40 patients were male. Patients in the SA group did not face post-operative pain till 8 hours. But patients in the GA group complained of postoperative pain after an hour of open cholecystectomy. The postoperative outcome included nausea or vomiting which was common in both groups and post-Dural headaches which were more common in patients of the SA group and was cured without giving any medication. The sore throat was more common in patients of the GA group. However, no respiratory depression was found in patients of both the SA as well as GA groups. Conclusion: Spinal anesthesia as compared to general anesthesia reveals longer pain-free hours and fewer adverse effects after open cholecystectomy. Nausea or vomiting was common in both groups, and no respiratory depression was found in patients from SA as well as the GA group. Open cholecystectomy needed training due to the factors that lead to conversion to laparoscopic surgery, such as incorrect anatomy and the onset of complications. Keywords: open cholecystectomy, anesthesia, spinal anesthesia, general anesthesia, postoperative outcome